Audit Committee Effectiveness Among Malaysian Listed Companies (Malaysian Management Journal, 1999)
This study investigates further the previous paper by Shamsul Nahar and Al-Murisi (1997) by examining the interactive effects of the variables in that paper and introducing other variables associated with corporate governance and political costs. The present study postulated that percentage of external directors on audit committee interacted with the presence of an accountant on audit committee and with the number of years an audit committee in existence, respectively, to influence audit committee effectiveness. The study also posited that the interaction of the presence of an accountant on audit committee and the number of years an audit committee in existence positively and significantly influenced audit committee effectiveness. Addition. ally, the roles of leadership structure, audit committee chairman, and a firm's size on audit committee effectiveness were also investigated. Using a multiple regression from a sample consisting the Kuala Lumpur Stock Exchange listed companies, results showed that only a firm's size significantly influenced audit committee effectiveness in the predicted direction. Other variables, on the other hand, did not show any significant influence on audit committee effectiveness.